A new species of Gonolobus (Apocynaceae, Asclepiadoideae, Gonolobineae) from Loja, Ecuador - Alvarado-Cárdenas, L.o.; Cerchiai, Alicia (Phytotaxa, 2022)
We here describe a new species of Gonolobus from southeastern Loja, Ecuador: Gonolobus rumihuilcanus. The species is morphologically similar to G. albomarginatus, G. leianthus, and G. saraguranus but differs in corolla and corona morphology, and distribution. A conservation status assessment, description, photographs, and a key to congeners in Ecuador are provided. The discovery increases to five the number of Gonolobus species reported for Ecuador, with three of them endemic.